Pemberdayaan Warga Rt. 07 Rw. 03 Kelurahan Penurunan Kota Bengkulu Melalui Edukasi Pengelolaan Sampah & Olahraga Bersama - Nada Chencelia; Dhea Ananda Saputri; Kevin Nicolas; Bagus Yudistira; Yenda Putri Otama; Yoli Andi Rozzi; Churin in; Karona Cahya Susena (Utami Publisher, 2026)
The low public awareness of waste management and the importance of physical activity remains a problem in urban residential areas. In RT 07 RW 03, Penurunan Village, Bengkulu City, household waste management has not been conducted optimally, and residents' participation in health activities is still limited. This community service activity aims to empower residents through education on waste management as well as organizing group exercise as an effort to increase community awareness of the environment and health. The methods used include initial condition observation, waste management counseling, waste sorting practice, and group exercise activities directly involving residents. The results of the activities show an increase in the community's understanding of household waste management, as well as greater participation in joint activities. In addition, group exercise serves as an effective means to strengthen social relationships and improve Awareness of the importance of a healthy lifestyle. Thus, environmental education combined with physical activity has been proven to be able to promote the holistic empowerment of the community.